Molecular Identification of Giardia Duodenalis Isolates from Children Stool in Diyala Province, Iraq - Mohymin Sabah Awad Awad, Tareq Rifaaht Minnat, Anas A. Humadi (Pakistan Journal of Medical & Health Sciences, 2022)
One of the most prevalent human intestine protozoan parasites in the world, Giardia duodenalis is indigenous to every continent and infects a broad variety of animal hosts. The goal of the current study was to determine the prevalence of infection among Giardia duodenalis isolates from regional hospitals and private clinics in the Iraqi province of Diyala that would be the subject of additional genetic analysis. From the beginning of October 2021 to the end of January 2022, 100 children’s stools were collected from hospitals and health centers in Diyala, Iraq. Additionally, Giardia duodenalis cysts and trophozoites were examined under the microscope, and DNA was extracted using Quick-DNA Fecal/Soil Microbe Kits. One hundred of the stools taken from youngsters show symptoms of diarrhoea, nausea, and abdominal pains Based on microscopic examination and PCR analysis, a 7 percent infection rate was discovered. In addition, genotyping was carried out utilizing G. duodenalis Tpi sequence analysis. The highest infection rate was 10 % in up 4-5 year category and the lowest infection rate 4.65% recorded in up one year category. While, the infection rate was highest in male samples 8.16% than female samples 5.88%. Regarding the giardiasis according to the house system, most people who were infected were living in the city centre at ratio 9.25%, followed by 4.34 % in persons living in the country side. On the other hand, the infection rate of Giardia infection was 6.89%,4.16% and 8.51% to the tap water, Reverse Osmosis(RO) water and filter water respectively. The findings of this study emphasize that area of study was G. duodenalis infection rate with source of infection route and water basis in children in this province. The genetic analysis of the region Beta-giardin and RH11 and TPIA in this study showed that this diagnosis of Giardia duodenalis was made after effective amplification of these regions. Keywords: Molecular, Infection rate, Risk factors, Giardia duodenalis.